PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE-FRIENDLY BERBASIS MIT APP INVENTOR UNTUK PENGUATAN MINAT BELAJAR SISWA DI SMK MUHAMMADIYAH 1 AJIBARANG - Mia Muliyawati; Eka Farida Fasha (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to develop a product in the form of learning media based on Mit App Inventor and to determine its role in strengthening students' learning interest. This study uses a 4D development model which includes several stages, namely the Define, Design, Development, Dissemination stages. This research was conducted at SMK Muhammadiyah 1 Ajibarang with a population of class XI and the sample used was 30 students of class XI AK 4. Data collection techniques used in this study were observation, interviews, questionnaires (questionnaires). Data analysis techniques used in this study were product validity and product practicality testing. The results of the study showed that the Mit App Inventor learning media developed obtained the eligibility criteria after passing the validation test stage by experts in the form of a media validation test by obtaining a percentage of 97% with a very valid category, and the material validation test obtained a percentage of 93% with a very valid category and in the practicality test with a student response questionnaire obtained a percentage of 87.4% with a very practical category.